Indirect emissions of forest bioenergy: detailed modeling of stump‐root systems. Issue 6 (27th May 2013) - Liski, Jari; Kaasalainen, Sanna; Raumonen, Pasi; Akujärvi, Anu; Krooks, Anssi; Repo, Anna; Kaasalainen, Mikko
Abstract Indirect carbon dioxide emissions from producing bioenergy from tree stumps and roots depend critically on the decomposition rate of these harvest residues if they were left in forest to decay. We developed a method to improve the current estimates of these emissions. First, the 3D structure of uprooted stump‐root systems was modeled based on terrestrial laser‐scanning data. Second, information obtained on the size distribution of the stumps and the roots was used to simulate their decomposition and to estimate the indirect emissions. The method was able to describe the structure of stump‐root systems at a clear‐cut boreal Norway spruce test site. Compared with earlier results based on the diameter of stumps alone, the new estimates of the decomposition rate were slightly higher and, consequently, those of the indirect emissions slightly lower. The method is useful to collect information on the indirect emissions of stump‐root bioenergy quickly in different forests.